Plant usage in landscape design - Clokey, Jora; Mullany, Steve; San Luis Video Publishing (Los Osos, California : San Luis Video Publishing, 2004)
xplains the importance of plants in the planned landscape, looking into their functional, aesthetic, property and environmental values. Shows how a site analysis aids the designer in choosing plants that are most appropriate to use on a particular site, and how to design with a maintenance plan. Explores space articulation and privacy; circulation; screening; vies and vista controls, erosion control; soil building; habitat for wildlife and people; and air quality. Discusses historic and cultural influences that often have an impact on design, and specific plant uses for various types of styles such as climate-adapted landscapes and other planting themes
Title from title screen
DVD format
Keywords: Landscape architecture; Landscape design; Plants